Sampling effects on the quantification of sodium content in infant formula using laser induced breakdown spectroscopy (LIBS) - Cama-Moncunill, Xavier; Markiewicz-Keszycka, Maria; Cama-Moncunill, Raquel; Dixit, Yash; Casado-Gavalda, Maria P.; Cullen, P.J.; Sullivan, Carl (Elsevier, 2018)
Laser-induced breakdown spectroscopy (LIBS) was employed to predict the sodium content of infant formula (IF) over the range 0.5–4 mg Na g−1. Calibration models were built using partial least squares regression (PLS), correlating the LIBS spectral data with reference Na content quantified by atomic absorption spectroscopy (AAS). The main aim of this study was to demonstrate the ability of LIBS as a rapid tool for quantifying sodium in IF, but also to explore strategies concerning the acquisition and pre-processing of LIBS spectra. A range of different pre-processing techniques, measuring depths (repetition of laser shots) and accumulations were conducted and evaluated in terms of PLS performance. The best calibration model was developed using the third-layer spectra normalised by the H I 656.29 nm emission line, yielding a coefficient of determination (R2) of 0.93, and root-mean-square errors (RMSE) of 0.37 and 0.13 mg g−1 for cross-validation and validation, respectively.